PENGARUH GOOD CORPORATE GOVERNANCE, ARUS KAS BEBAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PRAKTEK MANAJEMEN LABA (Studi Pada Perusahaan Yang Terdaftar di Jakarta Islamic Index) - Rezki Zurriah (Universitas Medan Area, 2017)
This research is about to find out the influence of good corporate governance, company size, free cash flow, leverage as the management practice in the public company that listed at Jakarta Islamic Index 2010-2014. Sampling is using purposive sampling, there are 12 company from 56 company from total 60 unit as observed. Analysis Method is using the secondary data from www.idx.co.id with double linear regration. The results show that institutional ownership, independence commisioner, size of the commisioner board, free cash flow, company size, and leverage simultaneously influence the management real profit. Partially, no significant influence to the real profit, but leverage have positive and significant to management real profit.Keywords: institutional ownership, free cash flow, leverage, profit